Depression and chest pain in patients with coronary artery disease. (1st March 2017) - Hayek, Salim S.; Ko, Yi-An; Awad, Mosaab; Del Mar Soto, Andrea; Ahmed, Hina; Patel, Keyur; Yuan, Michael; Maddox, Spencer; Gray, Brandon; Hajjari, Jamal; Sperling, Laurence; Shah, Amit; et al.
Abstract: Background: Depression is common in patients with coronary artery disease (CAD) and is associated with more frequent chest pain. It is however unclear whether this is due to differences in underlying CAD severity. We sought to determine [1] whether depressive symptoms are associated with chest pain independently of CAD severity, [2] whether improvement in depressive symptoms over time is associated with improvement in chest pain and [3] whether the impact of revascularization on chest pain differs between patients with and without depression. Methods and results: 5158 patients (mean age 63 ± 12 years, 65% male, 20% African American) undergoing cardiac catheterization completed the Seattle Angina Questionnaire (SAQ) and Patient Health Questionnaire-8 (PHQ-8) to assess angina severity and screen for depression, respectively, both at baseline and between 6 and 24 months of follow-up. We found significant correlations between PHQ-8 scores and angina frequency (SAQ-AF, r = − 0.28), physical limitation (SAQ-PL, r = − 0.32) and disease perception (SAQ-DS r = − 0.37, all P < 0.001), which remained significant after adjustment for clinical characteristics, CAD severity, and anti-depressant use. Improvement in depressive symptoms at follow-up was associated with improvement in angina subscales (SAQ-AF β 1.34, P < 0.001), SAQ-PL β 1.85, P < 0.001), and SAQ-DS (β 2.12, P < 0.001), independently of CAD severity or revascularization. Patients with depression who underwent revascularization had less improvement in chest pain frequency than those without depressive symptoms. Conclusions: Depression is associated with angina, independently of CAD severity. Patients with depression may not derive as adequate symptomatic benefit from revascularization as those without. Whether treatment of underlying depression improves chest pain needs to be further studied.